How Marketing Capabilities Influence The Choice Of The Entry Modes Into Foreign Markets And Host Country Selection - Costa, Thiago Chiorino (2020)
Goal: In this paper we analyze, conceptually, the influence of marketing capabilities as antecedents of two core decisions for the internationalization of firms: foreign entry mode and host market selection.Method: We utilize the typology of four types of marketing capabilities – specialized, multifunctional, architectural and dynamic - to observe how they may differently induce different choices regarding foreign host markets (location) and foreign entry modes.Main Results - We propose that higher order marketing capabilities induce internationalization to more developed markets and using entry modes that ensure greater control and commitment of resources and, conversely, that lower order marketing capabilities lead to the choice of similarly or less developed markets using entry modes that favor lower control and less commitment of resources.Relevance / Originality: Our work explores a possible relationship between companies' marketing capabilities and their influence on the choice of mode of entry into foreign markets and the selection of the destination country.Theoretical contributions: We thus complement extant research on the role of capabilities in the internationalization of firms, specifically delving into the capabilities that are closer to the market, in contrast to studies on technological knowledge-based competencies or innovation, operational or capabilities based on the ability to arbitrage across markets.